Taḥlīl Istirātījiyyāt al-Mu'allim fī Muwājahati Ikhtilāf al-Khalfiyyāt al-Ta'līmiyyah li Ṭullāb fī Ta'līm al-Mufradāt bi al-Madrasah al-'Āliyah al-Ḥukūmiyyah al-Ūlā Mīdān, Andūnisiyyā - Dara Afjunita Tanjung; Harun Al Rasyid (KURAS Institute, 2026)
This study is motivated by the differences in prior Arabic learning backgrounds between students from Islamic boarding schools and non-Islamic boarding schools in the Tenth-Grade Islamic Senior High School of State Islamic Senior High School 1 Medan (MAN 1 Medan), causing a gap in initial ability in mastering Arabic vocabulary. This study aims to determine the differences in initial ability of Islamic boarding school and non-Islamic boarding school students and analyze teacher strategies in dealing with these differences. This study uses a qualitative approach with a descriptive research type. Data collection techniques are carried out through observation, interviews, and documentation. Data are analyzed through data reduction, data presentation, and drawing conclusions, while the validity of the data is tested using triangulation techniques. The results of the study indicate that there are differences in vocabulary ability between Islamic boarding school and non-Islamic boarding school students. To address these conditions, teachers apply adaptive and varied learning strategies, such as drill methods, group learning, learning media, and mentoring for non-Islamic boarding school students, so that the vocabulary learning process can take place more effectively and in a balanced manner.